2020
DOI: 10.1097/corr.0000000000001330
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Financial Impact of Orthopaedic Sequelae of Intravenous Drug Use on Urban Tertiary-care Centers?

Abstract: Background Orthopaedic sequelae such as skin and soft-tissue abscesses are frequent complications of intravenous drug use (IVDU) and comprise many of the most common indications for emergency room visits and hospitalizations within this population. Urban tertiary-care and safety-net hospitals frequently operate in challenging economic healthcare environments and are disproportionately tasked with providing care to this largely underinsured patient demographic. Although many public health initiative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…6 Physician fees tend to be a smaller proportion of costs relative to facility costs, 40 and a lack of availability of physician fees is a common limitation in cost analyses. 6,18,19 Likewise, the percentage of costs attributable to prosthetics has been limited or not reported in previous studies, and our comorbid cohort likely had lower utilization than previously documented rates after trauma-related amputations. Overall, our cost estimates underestimate the total true costs.…”
Section: Figurementioning
confidence: 71%
See 1 more Smart Citation
“…6 Physician fees tend to be a smaller proportion of costs relative to facility costs, 40 and a lack of availability of physician fees is a common limitation in cost analyses. 6,18,19 Likewise, the percentage of costs attributable to prosthetics has been limited or not reported in previous studies, and our comorbid cohort likely had lower utilization than previously documented rates after trauma-related amputations. Overall, our cost estimates underestimate the total true costs.…”
Section: Figurementioning
confidence: 71%
“…17 Examples of indirect costs include administrative, building, maintenance, housekeeping, dietary, medical records, and resident salaries. Costs associated with these hospitalizations that were not captured by this methodology include physician fees—which are commonly unavailable in cost analyses, 6,18,19 outpatient rehabilitation, and prosthetic costs. The application of cost center-based CCRs to total charges is used by hospitals for cost-based reimbursement claiming because it reasonably estimates the average costs associated with hospital services.…”
Section: Methodsmentioning
confidence: 99%
“…In case 1, the patient had a history of IV drug abuse and smoking that likely contributed to his postoperative MSSA infection. Although the patient’s last use of IV drugs was unknown, IV drug abuse is associated with various musculoskeletal infections including skin and soft tissue complications ( 8 ). The association between cigarette smoking and delayed wound healing is well-studied in the literature ( 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings may stem from other medical and behavioral health comorbidities that are associated with IVDU alone, thus reaching beyond interventions specific to the treatment of spinal epidural abscesses. Nonetheless, Dwivedi et al [11] reported that the treatment of spinal epidural abscesses in patients with IVDU resulted in financial losses of USD 5768 per patient for the institutions providing care. Viewed in this light, the use of nonoperative management when it is indicated for patients with IVDU who have spinal epidural abscesses may result in savings for health centers treating these individuals and more efficient allocation of resources to other aspects of care such as cessation of drug use and treatment of associated medical comorbidities and mental health concerns.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to surgical management, IVDU is another factor whose effect on long-term charges associated with the care of spinal epidural abscesses is unknown. Intravenous drug users tend to be underinsured, and care of IVDU-associated infections is associated with financial costs to healthcare systems [11,29]. It is unknown if charges specific to spinal epidural abscesses are higher in patients with active IVDU and whether these differences persist in long-term management.…”
Section: Rationalementioning
confidence: 99%